PFAS: challenges and scientific perspectives in human health risk assessment - Janine Kowalczyk; Klaus Abraham; Christina August; Runa S. Boeddinghaus; James C. Y. Chan; Alexander Eckhardt; Tony Fletcher; Finnian Freeling; Bernd Göckener; Thorhallur I. Halldórsson; Dorte Herzke; Ron L. A. P. Hoogenboom; et al. (Archives of Toxicology, 2026)
To review recent advances in research on per- and polyfluoroalkyl substances (PFAS) and outline priority steps for risk assessment in consumer health protection, the German Federal Institute for Risk Assessment (BfR) organized the ‘International PFAS Conference’ in Berlin in October 2025. Building on the European Food Safety Authority's (EFSA) opinion in 2020, global research activities on PFAS have intensified. The conference was attended by 200 participants from 18 countries and covered topics such as analytical methods, human exposure, toxicokinetics, toxicity, and future perspectives. Given that there are more than 21,000 different PFAS in use, discussions highlighted the need for further data collection and a basis for prioritizing substances. Robust exposure assessment requires improved analytical methods combined with newly developed predictive tools to quantify, identify, and make better use of non-target data. Hazard characterization may benefit from the combined use of classic experimental data sets, epidemiological data, and new approach methodologies (NAMs) data. The participants emphasized the continuous need for refined data and proposed a systematic consolidation of global data on shared data platforms, accompanied by corresponding guidelines for data usage. In the final panel discussion, effective risk communication was identified as a critical challenge, necessitating clear and consistent messaging for the public and policymakers. The conference concluded with five key recommendations for future health risk assessments: prioritizing PFAS; improving analytical methods; promoting generation of robust data and data gap filling; promoting open science, including the development of shared data infrastructure and cross-institutional knowledge exchange; and strengthening risk communication. These recommendations aim to support transparent, evidence-based and effective PFAS consumer health risk management in the decades ahead.

P18-45 Toxicokinetic model for the transfer of aflatoxin B1/M1 in dairy cows using hierarchical Bayesian inference of multiple datasets - J.-L. Moenning; R. Pieper; J. Numata (Toxicology Letters, 2025)

P25-22 Human health risk assessment of per- and polyfluoroalkyl substances in hen's eggs from the German market - K. Sommerkorn; U. Pabel; C. Jung; S. Gängler; J. Numata; R. Pieper (Toxicology Letters, 2025)

Replanting and yield increase strategies for alleviating the potential decline in palm oil production in Indonesia - Jing Zhao; Andrew J. Elmore; Janice Ser Huay Lee; Izaya Numata; Xin Zhang; Mark A. Cochrane (Agricultural Systems, 2023)

Electronic cigarette vapor exposure exaggerates the pro-inflammatory response during influenza A viral infection in human distal airway epithelium - Niccolette Schaunaman; Taylor Crue; Diana Cervantes; Kelly Schweitzer; Harrison Robbins; Brian J. Day; Mari Numata; Irina Petrache; Hong Wei Chu (Archives of Toxicology, 2022)

Suitability of Wild Boar (Sus scrofa) as a Bioindicator for Environmental Pollution with Perfluorooctanoic Acid (PFOA) and Perfluorooctanesulfonic Acid (PFOS) - J. Kowalczyk; J. Numata; B. Zimmermann; R. Klinger; F. Habedank; P. Just; H. Schafft; M. Lahrssen-Wiederholt (Archives of Environmental Contamination and Toxicology, 2018)

Does the trace element composition of brown trout Salmo trutta eggs remain unchanged in spawning redds? - R. M. Gabrielsson; J. Kim; M. R. Reid; C. H. Stirling; M. Numata; G. P. Closs (Journal of Fish Biology, 2012)
The temporal stability of trace element concentrations in fertilized, artificially incubated anadromous brown trout Salmo trutta eggs and newly hatched fry was investigated. The anadromous status of the parental fish was confirmed using strontium isotopic analysis of otoliths. Whilst manganese concentrations in eggs varied over time, concentrations of aluminium, potassium, magnesium, strontium, barium and calcium were all unchanged 1 week and 6 weeks post‐fertilization as well as in recently hatched larvae. The results clearly suggest that the distinctive trace element signature present in the eggs and newly hatched larvae of anadromous S. trutta (typically characterized by high strontium, low barium) is stable over time. Therefore analysis of the trace element composition of eggs is concluded to be a cost‐effective and reliable method for determining the spatial and temporal extent of upstream spawning migration by anadromous salmonids. The temporal variability of at least one element in this study suggests the stability of untested multi‐element signatures cannot automatically be assumed.

Petrology and petrogenesis of carbonatitic rocks in syenites from central Anatolia, Turkey - Alan F. Cooper; Durmus Boztuğ; J. Michael Palin; Candace E. Martin; Mihoko Numata (Contributions to Mineralogy and Petrology, 2011)

Hepatic cytochrome P450 activity and pollutant concentrations in paradise shelducks and southern black-backed gulls in the South Island of New Zealand - Mihoko Numata; J. Paul Fawcett; Dorothy J. Saville; Rhonda J. Rosengren (Ecotoxicology, 2008)